Challenges to Elephant Connectivity From Border Fences in the World's Largest Transfrontier Conservation Area - Naidoo, Robin; Beytell, Piet; Brennan, Angela; Kilian, Werner; McCulloch, Graham; Stronza, Amanda; Taylor, Russell; Tsholofelo, Chief; Songhurst, Anna (Frontiers in Conservation Science, 2022)
To more effectively protect biodiversity and promote sustainable development, transfrontier conservation areas (TFCAs) aim to enhance wildlife flows across national borders. This is true of the world's largest terrestrial TFCA, the Kavango-Zambezi (KAZA), home to half of Africa’s savannah elephants that move across five countries in a mixed-use landscape. We used GPS tracking data from > 100 collared elephants to evaluate how fences between Namibia and Botswana impact transboundary connectivity in KAZA. For female elephants these fences formed an impenetrable boundary, with no exchange between animals collared in Botswana and those collared in Namibia. Male elephants did cross border fences, although they remained a partial boundary, with 7 of 21 males accounting for most crossings. Our results suggest a review of fence alignment and de-commissioning of some fencing separating Namibia and Botswana, combined with increased support for fence-free interventions that reduce wildlife-livestock interactions, should be considered to meet the objectives of KAZA.